Prevalence of smartphone addiction and its association with depression, anxiety among university students, Baghdad 2023 - Algburi, Aya Salah Mahdi; Yassin, Batool Ali Ghalib (International Journal of Research in Medical Sciences, 2024)
Background: Smartphones have simplified our lives and become essential, yet excessive usage may lead to "smartphone addiction". Global youth smartphone addiction is a growing public health concern. Research examines smartphone addiction, depression, anxiety, and depression among university of Baghdad medical and non-medical students. Compare 2 student groups' smartphone addiction rates. Correlate smartphone addiction, anxiety, and depression. Methods: Comparative cross-sectional research included 383 university of Baghdad students from four colleges. The research included undergraduate university students for a random sampling. From March to June 2023, the smartphone addiction scale-short version (SAS-SV), Beck's depression inventory (BDI), Beck's anxiety inventory (BAI), and sociodemographic were self-reported. Results: This survey comprised 383 students, 188 (49.1%) from medical institutions and 195 (50.9%) from non-medical colleges. Their ages varied from 18-25, with a mean of 20.8±1.8 years. Most were 20-21 (37.9%) and 260 (67.9%) females. According to SAS-SV cutoffs, 45.17% of medical students and 39.5% of non-medical students were smartphone addicts. Depression affected 38.37% of individuals, ranging from mild (10.7%) to moderate (17.75%) to severe-very severe (9.92%). Survey revealed 50.65% had little anxiety, 31.07 moderate anxiety, and 18.28% severe anxiety. Smartphone addiction significantly correlated with anxiety (p=0.0001) and sadness (p=0.008). Smartphone addiction, anxiety (r=0.29), and depression (r=0.25), among research participants, were positively correlated. Conclusions: Smartphone addiction was common among study participants, with medical college students being more hooked than non-medical students. Smartphone addiction is correlated with anxiety and despair. Smartphone addiction predicted anxiety and despair.